2001
DOI: 10.1128/jb.183.23.6947-6950.2001
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Expression in Klebsiella pneumoniae and Shigella flexneri Using a Bacteriophage P1-Derived C1-Regulated Promoter System

Abstract: The utility of promoters regulated by the bacteriophage P1 temperature-sensitive C1 repressor was examined in Shigella flexneri and Klebsiella pneumoniae. Promoters carrying C1 operator sites driving LacZ expression had induction/repression ratios of up to 240-fold in S. flexneri and up to 50-fold in K. pneumoniae. The promoters exhibited remarkably low basal expression, demonstrated modulation by temperature, and showed rapid induction. This system will provide a new opportunity for controlled gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…Moreover, the results suggested that differences in C1 expression correlated with the ability to achieve derepression. Partial derepression when the repressor is in excess has been demonstrated previously for regulated promoter systems in gram-negative bacteria (33,45). Indeed, ProA might be expected to be more active than ProB, resulting in higher levels of C1 expressed, since it contains more conserved nucleotides.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the results suggested that differences in C1 expression correlated with the ability to achieve derepression. Partial derepression when the repressor is in excess has been demonstrated previously for regulated promoter systems in gram-negative bacteria (33,45). Indeed, ProA might be expected to be more active than ProB, resulting in higher levels of C1 expressed, since it contains more conserved nucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure efficient translation, the primers amplifying lacZ incorporated a contrived RBS derived from gram-positive species (6). This resulted in a 200-fold increase in ␤-Gal activity in E. faecalis (data not shown) compared to that with the lacZ RBS (GGA GG[N] 6 ATG) used for reporter gene studies of gram-negative bacteria (45); consequently, the former RBS was also incorporated into the forward primers amplifying c1 and bof. At the permissive temperature, C1 binds to its operator sites and prevents transcription from the reporter gene, while at the nonpermissive temperature, C1 is thermally unstable, thereby allowing transcription to proceed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations